Fairest of all - Valentino, Serena; Marchbank, Fiona (Los Angeles : Disney Hyperion, 2023)
Examines the life of Snow White's stepmother, the Wicked Queen, to find out just what it is that makes her so evil that she would want to cut out her teenage step-daughter's heart and have it delivered in a locked keepsake box.
Keywords: Good and evil -- Comic books, strips, etc; Fairy tales